2016
DOI: 10.1111/mmi.13455
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of Campylobacter jejuni flagellin levels through reciprocal binding of FliW to flagellin and the global regulator CsrA

Abstract: Summary Bacterial flagella assembly is tightly regulated to ensure a timely and sequential production of the various flagellum constituents. In the pathogen Campylobacter jejuni the hierarchy in flagella biosynthesis is largely determined at the transcriptional level through the activity of the alternative sigma factors sigma54 and sigma28. Here, we report that C. jejuni flagellin levels are also controlled at the post‐transcriptional level via the thus far poorly‐characterized flagellar assembly factor FliW. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
(92 reference statements)
0
28
0
3
Order By: Relevance
“…These studies also showed that while acetate activates expression of invasion genes, butyrate and propionate function to repress expression of invasion genes, demonstrating that different SCFAs have opposite effects on invasion gene expression (40, 65). Although C. jejuni produces CsrA, which affects expression and translation of some virulence and colonization genes, it lacks homologs of the BarA/UvrY system, CsrB, CsrC, and HilD (6669). Thus, C. jejuni employs a different system than E. coli and Salmonella species to sense and respond to these metabolites in the chick intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also showed that while acetate activates expression of invasion genes, butyrate and propionate function to repress expression of invasion genes, demonstrating that different SCFAs have opposite effects on invasion gene expression (40, 65). Although C. jejuni produces CsrA, which affects expression and translation of some virulence and colonization genes, it lacks homologs of the BarA/UvrY system, CsrB, CsrC, and HilD (6669). Thus, C. jejuni employs a different system than E. coli and Salmonella species to sense and respond to these metabolites in the chick intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…8). This included the filament chaperone gene fliW 13, 62 and the flagellar cap fliD . A FliD subunit vaccine induced a transient but significant reduction (~2 log) of C .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting PCR fragment was cloned directly into pSCODON1.2 with the use of NdeI and XhoI restriction enzymes, yielding pSCODON1.2-FliS. The cloning of C. jejuni racR gene to pSCODON1.2 vector has been described elsewhere (Radomska et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…EcoRI and XhoI sites present in the MCS of the vector were used for cloning. The cloning of fliW gene to pGEX4T-2 expression vector has been described elsewhere (Radomska et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation